Люблю твои воспоминания: роман / С. Ахерн ; пер. с англ. М. Бабичевой - Ахерн Сесилия (Иностранка, 2011)
Экземпляры: аб. (2012) / Инвентарный номер: 54175 / Цена: / Сис.шифр: 84(4Ирл)-4 / Авт.знак: А 95 / ГРНТИ: 17.82.31 / ББК: 84(4Ирл)-44^VLBC/RL